Implementation of WHO guidelines for cervical cancer screening, diagnosis and treatment: knowledge and perceptions of health providers from Argentina - Arrossi, Silvina (2024)
Background The 2021 World Health Organization (WHO) guidelines on cervical cancer screening and treatment provide countries with evidence-based recommendations to accelerate disease elimination. However, evidence shows that health providers’ adherence to screening guidelines is low. We conducted a study in Argentina to analyze health providers’ knowledge and perceptions regarding the 2021 WHO Guidelines. Methods A qualitative study was conducted based on individual, semi-structured interviews with health providers specializing in gynecology (n=15). The themes explored were selected and analyzed using domains and constructs of the Consolidated Framework for Implementation Research. Results Although health providers perceive WHO as a reliable institution, they do not know the 2021 guidelines, its supporting evidence, and its elaboration process. Their clinical practice is mainly guided by local recommendations developed by national professional medical associations (PMAs). For interviewees, WHO guidelines should be disseminated through health authorities and national PMAs, mainly through in-service training. Health providers had a positive assessment regarding WHO Recommendation 1 (screen, triage, and treatment for women aged 30+with HPV-testing every 5 to 10 years) and perceived a favorable climate for its implementation. HPV-testing followed by triage was considered a low-complexity practice, enabling a better detection of HPV, a better selection of the patients who will need diagnosis and treatment, and a more efficient use of health system resources. However, they suggested adapting this recommendation by removing screening interval beyond 5 years. WHO Recommendation 2 (screen-and-treat approach with HPV-testing for women aged 30+every 5 to 10 years) was predominantly rejected by interviewees, was considered an algorithm that did not respond to women’s needs, and was not adequate for the Argentinean context. Regarding the HPV-test modality, clinician-collected tests were the preferred mode. Health providers considered that HPV self-collection should be used primarily among socially vulnerable women to increase screening coverage. Conclusion WHO guidelines should be widely disseminated among health providers, especially in settings that could benefit from a screen-and-treat approach. Identifying areas of partnership and collaboration with PMAs in implementing WHO guidelines is essential.